Prevalence of falls and its associated factors among elderly diabetes attending klinik pakar perubatan and klinik rawatan keluarga Hospital Universiti Sains Malaysia - Hasniza, Hasim (2009)
To assess the prevalence of fall and its associated factors among elderly diabetes type 2 attending outpatient clinics (KPP&KRK}, HUSM. This is a cross sectional study conducted in outpatient clinic HUSM from April 2007 till March 2008, among 288 elderly diabetes type 2. The patient was selected using systematic random sampling method. Baseline data on socio-demographic, diabetes history, comorbid diseases, drugs use and activity of daily living (Barthel's index) were performed. The patient also was examined physically and balance and gait assessment was carried out. Review of patient's medical record for laboratory investigations result and medication and concomitant illness were also done. Falls was defined having at least one history of falls in the past one year from the interview date. Prevalence of falls among elderly diabetes was 18.8 %. Among the faller group, 72.2 % had more than one falls. Female gender (OR: 2.54, p<0.05), age group more than 75 (OR: 2.97, p<0.05), retinopathy (OR: 2.19, p<0.05}, orthostatic hypotension (OR: 2.87, p<0.05) were associated with higher risk for falls. High balance and gait score was associated with reduced risk of fall in elderly diabetes (OR: 0.89, p<0.05). In this cross sectional study among elderly diabetes type 2, the prevalence of falls were found to be lower compared to previous study in the western countries. The factors that associated with higher risk for fall were female sex, age group more than 75, presence of retinopathy and orthostatic hypotension. Those who had higher Balance and Gait score were found to be less likely to fall compare with those with lower score.